The Dominant Personality Type in Patient with Hypertension at Dr. Soetomo General Hospital Based on The Big Five Personality Theory - Chorisma Permata Putri Nurazizah; Abdurachman Abdurachman; Soetjipto Soetjpto; Yudi Her Oktaviono; Luqman Hakim Andira (Humanistic Network for Science and Technology (HNST), 2020)
Introduction: Hypertension which reaches 1.13 billion people in the world is a major risk factor of global death. One of the factors of hypertension is a lifestyle that is highly favored by personality. Therefore, it is necessary to do research on the dominant personality in people with hypertension. Purpose: To identify the dominant personality type according to Big Five Personality in patietns with hypertension in RSUD Dr. SOetomo Surabaya in September 2019. Methods: The research’s method was descriptive research. The sample of this research was patient with hypertension in Outpatient Clinic RSUD Dr. Soetomo Surabaya in September 2019. Personality variables were identifyed by Big Five Personality questionnaire. After the data was collected, the dominant personality type was determined by looking for mode. Results: According to Big Five Personality, the dominant personality in patients with hypertension in RSUD Dr. Soetomo Surabaya, September, 2019 period was Openness. Keywords: big five personality; hypertension; personality type; openness